Penerapan TOPSIS sebagai Penentu Kenaikan Gaji Karyawan di Perusahaan Alpha - Sari, Renny Puspita; Hartoyo, Andre (Jurnal Teknologi dan Manajemen Informatika, 2022)
Employee salary increases are common and have become a right of employees that must be fulfilled by the company if they do their job well. However, in this matter, it is not easy for companies to determine which employees will receive their salary increases. One of them is the Alpha company which has problems in determining employee salary increases which are still carried out without a calculation process so that there is a gap between employees. Therefore, an effective and fast Decision Support System is needed to determine decisions by applying the TOPSIS method as the basis for calculating the decision results. Â To assess this system, functional testing has been carried out on the Alpha company and obtained a result of 84.67% showing transparency in determining employee salary increases.